2012
DOI: 10.1097/ta.0b013e31823f0465
|View full text |Cite
|
Sign up to set email alerts
|

Emergency uncrossmatched transfusion effect on blood type alloantibodies

Abstract: High rates of injury recidivism in trauma patients increase the likelihood of multiple blood transfusions during their lifetime. Rh- patients who receive Rh+ blood are at risk of developing anti-Rh antibodies, putting them at risk for HTR. The conservation of Rh- blood for use in female patients may be detrimental to Rh- male patients. Laboratory diagnostic criteria for HTR are nonspecific in the trauma population and should be used with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…This approach is supported by data from the US demonstrating that blood supply with non-cross-matched units of RBCs is safe in trauma patients [6,7,8,9,10,11,12]. Transfusion with RhD+ RBCs does not increase the rate of hemolytic transfusion reactions disproportionally [12].…”
Section: Introductionsupporting
confidence: 49%
See 1 more Smart Citation
“…This approach is supported by data from the US demonstrating that blood supply with non-cross-matched units of RBCs is safe in trauma patients [6,7,8,9,10,11,12]. Transfusion with RhD+ RBCs does not increase the rate of hemolytic transfusion reactions disproportionally [12].…”
Section: Introductionsupporting
confidence: 49%
“…Other studies [3,8,9,11] reported well lower exposure rates (6-7%), partially, because a limited number of RhD- units was also available in the ER [3,8,9]. The British Guidelines recommend to use no more than 2 units of RBCs for patients with unknown blood group [23] and to switch to RhD+ units in men, women of not childbearing age, and in MTPs, a recommendation that was implemented in many trauma centers [24].…”
Section: Discussionmentioning
confidence: 99%
“…The MDmulticard Basic Extended Phenotype might become an equal or even superior alternative for such purposes. Moreover, the MDmulticard system could not only be adequate for blood typing in emergency situations [4,8,9,10] and extreme environment conditions [22], but could also be more cost-effective, as it limits the number of genotyping investigations necessary (and therefore the costs) to provide antigen-matched blood, especially for patients with autoantibodies or sickle cell disease. However, this should be confirmed by studies specifically aimed to cost and time analyses [23].…”
Section: Discussionmentioning
confidence: 99%
“…The development and improvement of tools for rapid and reliable blood typing adequate for use in acute clinical situations is warranted [4]. In a step further to the MDmulticard that determines a patient's main antigens (ABO, Rh phenotype and K) within a few minutes [7], the new MDmulticard Basic Extended Phenotype covers an additional array of clinically significant antigens [11] through the same lateral flow principle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation